Prevalence, factors and consequences of dating violence in a tertiary institution in Southern Nigeria - Iwemjiwe, Christian N.; Okojie, Hilda O. (International Journal Of Community Medicine And Public Health, 2016)
Background: Dating violence occurs in a relationship and may have immediate as well as long term implications for victims, perpetrators, family and community. This study aimed to identify the prevalence of the different components or various types of dating violence, factors associated with dating violence and effects of dating violence on undergraduates in University of Benin. Methods: The study was carried out in the campuses of University of Benin, Benin City. A cross-sectional descriptive study method was used and the study lasted for three months. Data were generated through the use of self-administered questionnaires distributed to respondents in all faculties and schools. A total of 400 respondents were selected using stratified sampling technique. Data were analysed with statistical package for social sciences software SPSS version 16. Results: The findings showed a prevalence of 76.4% for dating violence. The highest number of reported cases was in the age range 19-24 years. There was a significant association between dating violence and age, sex, and co-habiting of partners of the respondents. Dating violence was not dependent on residence of the respondent. Physical violence was the highest suffered by the respondents 54.4%, while sexual violence was the least 23.3%. Conclusions: The study has established that dating violence is a problem in the University which needs to be prevented through school-based education and awareness programmes.